(untitled) (Al-Aasar, 2025)
Punjabi poetry has long served as a mirror to the cultural, political, and social realities of its time. While male poets have historically dominated this literary tradition, the contributions of women, particularly ”طبع زاد شاعرات“ (unpublished or emerging women poets), have been equally significant. These poets have not only enriched Punjabi literature but have also used their verses to engage with pressing political, societal, and communal issues. From the spiritual and reformist poetry of Baba Farid to the works of modern-day poets, Punjabi literature has consistently intertwined themes of love, identity, and resistance with a deeper focus on societal transformation. This tradition is carried forward by unpublished Punjabi women poets, whose works reflect a conscious effort to address gender inequality, political oppression, and communal harmony. Their poetry often serves as a voice for the marginalized, challenging stereotypes and advocating for social justice.This study aims to explore the multifaceted dimensions of political, societal, and communal themes in the poetry of these emerging women poets. By analyzing their works, it seeks to highlight how they navigate and reinterpret the complexities of contemporary Punjab while staying rooted in its rich literary heritage. Through their verses, these poets not only preserve the cultural legacy of Punjab but also redefine its relevance in the modern world, making their contributions indispensable to the ongoing discourse on social and political change.